Digital-based zakat management from a good governance perspective at BAZNAS Muara Enim - Febriansyah, Febriansyah; Handayani, Rizqi; Rahman, Yusuf; Maswani, Maswani (Review of Islamic Social Finance and Entrepreneurship, 2026)
Purpose – This study aims to analyze the role of digital zakat management based on the BAZNAS Management Information System (Sistem Informasi Manajemen BAZNAS, SIMBA) application in strengthening good governance practices at the BAZNAS Muara Enim Regency. Methodology – This research uses a qualitative approach with a case study method. Data collection techniques included in-depth interviews, observations, and documentation. Data analysis was descriptive-analytical, using a good governance perspective that emphasizes the principles of transparency, accountability, and responsiveness. Findings – The research results show that the implementation of SIMBA not only functions as an internal administrative and managerial instrument but also serves as a technology-based public governance mechanism. SIMBA contributes to increasing transparency through information disclosure and a digital reporting system, enhancing accountability through integrated and accountable zakat data recording and management, and encouraging the responsiveness of services that are fast and efficient in responding to public information needs and requests. However, SIMBA implementation still faces limitations, particularly related to human resource capacity and digital literacy among service users. Implications – This research can serve as a reference for zakat institutions by expanding the study of digital-based management from a good governance perspective. Originality – The research can make a practical contribution to zakat management institutions by optimizing the use of digital systems as an instrument for strengthening governance and improving the quality of public services.